Analysis of Export Competitiveness of Main Commodities of North Sulawesi Province - Fahrudin Zain Olilingo; Nur Aini Umar; Ivan Rahmat Santoso (Jurnal Ekonomi dan Studi Pembangunan, 2024)
This study describes the competitiveness of the main Commodity Exports of North Sulawesi Province. This research is quantitative in nature, using secondary data obtained from the Central Statistics Agency (BPS) in the form of time series with a period of 5 years (2017-2021); the type of data used is the realization of the export value of the four main commodities of North Sulawesi 2017-2021. This research uses Revealed Comparative Advantage (RCA) analysis. The results of this study indicate (1) commodities identified as the most superior commodities of North Sulawesi, namely the commodity Animal/vegetable fats & oils, commodities fish and shrimp, meat commodities, and processed fish commodities, have high competitiveness with an RCA value> 1. (2) The results of the analysis show that the various chemical products group in 2017 has a weak competitiveness RCA value < 1 but when viewed from the average RCA value for five years the commodity of various chemical products has an RCA value> 1.